ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DALAM MENUNJANG EFEKTIVITAS PENGENDALIAN INTERN PADA CV. KOPI RANDU - Vitaloka, Risvy Irma Dyah; Ambarwati, Lilik; Syaflan, Meidi (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This research was conducted with the aim of knowing how the payroll information system and further analyzing the payroll accounting system procedures that are applied can support internal control at CV. Randu Coffee. The methods used in this research are interviews, observation, and documentation. The data analysis technique used is a qualitative descriptive analysis technique which is a technique by describing the payroll information system that exists within the company such as related functions, documents, accounting records used, a network of procedures that form a payroll information system, and elements of internal control. payroll information system. After all data has been collected and also analyzed, an evaluation is then carried out whether the payroll information system applied to the company can increase the effectiveness of internal control or not. The results of the research turned out to show that the implementation of payroll systems and procedures on CV. Randu's copy to fulfill the elements and objectives of the internal control of the payroll information system is still not effective. This can be seen from the presence of dual tasks in the HRD section, thus allowing for acts of fraud and also frequent human errors in the preparation of payroll reports which double as timekeepers, makers of payroll registers, and also carry out payment of salaries to each employee, as well as there is no special section that should oversee the attendance process when employees input attendance using the finger print tool.